Differential expression of epigenetic modifiers in early and late cardiotoxic heart failure reveals DNA methylation as a key regulator of cardiotoxicity - Robinson, Emma L.; Ameri, Pietro; Delrue, Leen; Vanderheyden, Marc; Bartunek, Jozef; Altieri, Paola; Heymans, Stephane; Heggermont, Ward A. (Frontiers in Cardiovascular Medicine, 2023)
Background Anthracycline-induced cardiotoxicity is a well-known serious clinical entity. However, detailed mechanistic insights on how short-term administration leads to late and long-lasting cardiotoxicity, are still largely undiscovered. We hypothesize that chemotherapy provokes a memory effect at the level of epigenomic DNA modifications which subsequently lead to cardiotoxicity even years after cessation of chemotherapy. Methods We explored the temporal evolution of epigenetic modifiers in early and late cardiotoxicity due to anthracyclines by means of RNA-sequencing of human endomyocardial left ventricular biopsies and mass spectrometry of genomic DNA. Based on these findings, validation of differentially regulated genes was obtained by performing RT-qPCR. Finally, a proof-of-concept in vitro mechanistic study was performed to dissect some of the mechanistic aspects of epigenetic memory in anthracycline-induced cardiotoxicity. Results Correlation of gene expression between late and early onset cardiotoxicity revealed an R2 value of 0.98, demonstrating a total of 369 differentially expressed genes (DEGs, FDR < 0.05). of which 72% (n = 266) were upregulated, and 28% of genes, (n = 103) downregulated in later as compared to earlier onset cardiotoxicity. Gene ontology analysis showed significant enrichment of genes involved in methyl-CpG DNA binding, chromatin remodeling and regulation of transcription and positive regulation of apoptosis. Differential mRNA expression of genes involved in DNA methylation metabolism were confirmed by RT-qPCR in endomyocardial biopsies. In a larger biopsy cohort, it was shown that Tet2 was more abundantly expressed in cardiotoxicity biopsies vs. control biopsies and vs. non-ischemic cardiomyopathy patients. Moreover, an in vitro study was performed: following short-term doxorubicin treatment, H9c2 cells were cultured and passaged once they reached a confluency of 70%–80%. When compared to vehicle-only treated cells, in doxorubicin-treated cells, three weeks after short term treatment, Nppa, Nppb, Tet1/2 and other genes involved in active DNA demethylation were markedly upregulated. These alterations coincided with a loss of DNA methylation and a gain in hydroxymethylation, reflecting the epigenetic changes seen in the endomyocardial biopsies. Conclusions Short-term administration of anthracyclines provokes long-lasting epigenetic modifications in cardiomyocytes both in vivo and in vitro, which explain in part the time lapse between the use of chemotherapy and the development of cardiotoxicity and, eventually, heart failure.